Laserscanning e 3D Modelling nell’archeologia urbana: lo scavo della chiesa di Sant’Agata al Carcere a Catania (Italia) - L. Arcifa; D. Cali; A. Patanè; F. Stanco; D. Tanasi; L. Truppia (Virtual Archaeology Review)
Urban archaeology undoubtedly represents the most problematic branch of archaeological research, due to the many problems of conservation and promotion of the evidence. A significant example is presented by the excavations carried out by the Superintendency for Cultural Goods of Catania in the church of “Sant’Agata al Carcere”, located in the heart of down town Catania. The most important discovery of the archaeological campaign was part of a ruined archaic wall in polygonal technique, located in the western side of the sacristy of the “Sant’Agata al Carcere” church. Furthermore, a late hellenistic votive deposit located within a pit, contained two small jars and a lidded stamnos, was discovered between the stones of the fallen wall. The excavations were performed during the restoration of the church. After the restoration, due to the special function of the building, it was necessary to quickly re-open the churches, thereby hiding the archaeological monuments from public view. In this perspective, a virtual museum project was implemented by an equipe of archaeologists and information technologists of the Archeomatica Project of Catania University, in order to display the important discoveries from the sacristy, which were covered up by the re-location of the floor in situ, applying both laser-scanner and 3D modelling techniques.